Online Learning in a South African Higher Education Institution: Determining the Right Connections for the Student - Queiros, Dorothy; de Villiers, Mary (International Review of Research in Open and Distributed Learning, 2016)
Online learning is a means of reaching marginalised and disadvantaged students within South Africa. Nevertheless, these students encounter obstacles in online learning. This research investigates South African students’ opinions regarding online learning, culminating in a model of important connections (facets that connect students to their learning and the institution). Most participants had no prior experience with online learning. Their perceptions and barriers to learning may apply to other developing countries as well.A cross-sequential research design was employed using a survey among 58 fourth-year students who were studying a traditional paper-based module via open distance learning. The findings indicated certain essential connections: first, a strong social presence (through timely feedback, interaction with facilitators, peer-to-peer contact, discussion forums, and collaborative activities); second, technological aspects (technology access, online learning self-efficacy, and computer self-efficacy); and third, tools (web sites, video clips). The study revealed low levels of computer/internet access at home, which is of concern in an ODL milieu heading online. Institutions moving to online learning in developing countries should pay close attention to their students’ situations and perceptions, and develop a path that would accommodate both the disadvantaged and techno-savvy students without compromising quality of education and learning. The article culminates in practical recommendations that encompass the main findings to help guide institutions in developing countries as they move towards online teaching and learning.